2007
DOI: 10.1038/sj.jhh.1002233
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of fibrinogen and C-reactive protein are related to interleukin-6 gene −572C>G polymorphism in subjects with and without hypertension

Abstract: Hypertension is an important risk factor for cardiovascular diseases. There is increasing evidence suggesting that inflammation is involved in the development of hypertension. Interleukin-6 (IL-6) is an important mediator of inflammatory response and the major regulator of hepatic production of acute phase proteins, such as fibrinogen and C-reactive protein (CRP), which have been associated with hypertension and cardiovascular diseases. Therefore, we studied the association of single nucleotide polymorphism (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…In accordance to our findings, no significant differences were found between IL-6 -174 G/C and -572 G/C polymorphisms and HT whereas some other studies showed relations between IL-6 -174 G/C polymorphism and HT and also cardiovascular diseases (CVD) (Humphries et al 2001;Timasheva et al 2008;Losito et al 2003;Pola et al 2002;Wong et al 2007). …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In accordance to our findings, no significant differences were found between IL-6 -174 G/C and -572 G/C polymorphisms and HT whereas some other studies showed relations between IL-6 -174 G/C polymorphism and HT and also cardiovascular diseases (CVD) (Humphries et al 2001;Timasheva et al 2008;Losito et al 2003;Pola et al 2002;Wong et al 2007). …”
Section: Discussionsupporting
confidence: 77%
“…Polymorphisms -174 G/C and -572 G/C were shown to be associated with plasma IL-6 (Humphries et al 2001;Fishman et al 1998;Losito et al 2003) and CRP levels (Humphries et al 2001;Losito et al 2003;Wong et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative results could be explained in a number of ways. First, EH is not a single entity; rather, it is likely to result from the interaction between environmental factors and a genetic predisposition to many polygenic quantitative traits acting in concert in various combinations in different individuals (26). The contribution of the -634c>g polymorphism to EH may therefore be so small that our study simply lacked the power to detect it.…”
Section: Discussionmentioning
confidence: 64%
“…After adjusting for covariates and post-hoc analysis, only rs3091244 SNP was associated with prevalent CAD, particularly in the non-Hispanic White population [46]. In a more recent analysis of data pooled from 5 different studies comprising of 4610 CAD patients and over CIMT [32] High CRP levels [22,52,53,55] PAD [33] High Systolic Blood pressure [27] Increased arterial stiffness [28] Insulin insensitivity [84] Lipid abnormalities [34] -572G>C rs1800796 CAD / MI [38] High plasma IL6 levels [24] Plasma IL6, CRP, Fibrinogen [54] CRP +1444C>T rs3091244 CAD [46] High plasma CRP levels [42,45,52,85,86] Stroke [87] Hypertension [47] Obesity [50] rs3093058 High Plasma CRP levels [86] rs3091244 High Plasma CRP levels [49] rs1800947 Arterial pulse-wave velocity [49] TNF-α -308G>A rs3091256 CAD [58,60,61,66,67] Obesity [63] Insulin resistance [64] Metabolic syndrome [62] Plasma CRP levels [65] CAD -Coronary Artery Disease, CIMT -Carotid Intima Media Thickness, CRP-C-reactive protein, IL 6 -Interleukin 6, MI-Myocardial Infarction, PAD -Peripheral Arterial Disease, SNP -Single Nucleotide Polymorphism, TNF-α -Tumor necrosis factor-alpha. Note: References given in brackets.…”
Section: Crp Gene Polymorphismsmentioning
confidence: 99%